Effects of television on academic performance and languages acquisition of pre-school children - Ahinda, Avosa Arthur; Murundu, Zadock Obuchere; Okwara, Michael O.; Odongo, Benson Charles; Okutoyi, Joel (IJERN, 2011)
Pre-school children come into daily contact with various forms of mass media which influence their academic and social behaviour. Though television has been used to play a monumental role in promotion of education and entertainment, children with full exposure to television have been found to perform poorly in class and fail to speak languages fluently. Public confidence in it is in question as many stakeholders have expressed concern about the amount of television and the type of programming to which children are being exposed to.The purpose of the study was to investigate the effects of television on academic performance and languages acquisition of pre-school children in Tiriki East Division, Hamisi Sub-County, Vihiga County, Kenya. The study involved 40 teachers and 132 parents drawn from 20 pre-schools selected by simple random technique. It employed descriptive survey design and an ex-post facto research design. Data was collected by questionnaires. The study found out that; Television watching has a negative effect on both academic achievement and languages acquisition of pre-school children. The study recommends that; both parents and teachers should be involved in the choice and selection of appropriate and educative Television programs for pre-school children.
Keywords: Pre-School children effect; Television; Academic performance; Language acquisition